Molecular Imaging of Ulex Europaeus Agglutinin in Colorectal Cancer Using Confocal Laser Endomicroscopy (With Video) - Wang, Weijun; Tian, Shuxin; Jiang, Xin; Pang, Suya; Shi, Huiying; Fan, Mengke; Wang, Zeyu; Jiang, Weiwei; Hu, Weiqian; Xiao, Xueyan; Lin, Rong (Frontiers in Oncology, 2021)
Background and study aims: Previous studies have identified that colorectal cancer has different fucosylation levels than in the normal colon. Ulex europaeus agglutinin-I (UEA-I), which specifically combines with α1-2 fucose glycan, is usually used to detect fucosylation levels. Therefore, we used confocal laser endomicroscopy (CLE) to investigate fluorescently labeled UEA-Fluorescein isothiocyanate (FITC) for detecting colonic cancer. Patients and methods: We stained frozen mouse colon tissue sections of normal, adenoma, and adenocarcinoma species with UEA-FITC to detect fucosylation levels in different groups. White light endoscopy and endocytoscopy were first used to detect the lesions. The UEA-FITC was then stained in the mice and human colon tissues in vitro. The CLE was used to detect the UEA-FITC levels of the corresponding lesions, and videos were recorded for quantitation analysis. The diagnostic accuracy of UEA-FITC using CLE was evaluated in terms of sensitivity and specificity. Results: The UEA expression level in colorectal cancer was lower than that in normal intestinal epithelium. The fluorescence intensity ratio of UEA-FITC in colorectal cancer was significantly lower than that in normal tissue detected by CLE in both mice and humans. The combination of UEA-FITC and CLE presented a good diagnostic accuracy with a sensitivity of 95.6% and a specificity of 97.7% for detecting colorectal cancer. The positive and negative predictive values were 91.6% and 95.6%, respectively. Overall, 95.6% of the sites were correctly classified by CLE. Conclusions: We developed a new imaging strategy to improve diagnostic efficacy of CLE by using UEA-FITC.